FIRST YEAR LEARNER NURSES’ PERCEPTIONS ON LEARNING MOTIVATION IN SELF-DIRECTED LEARNING IN A SIMULATED SKILL LABORATORY AT A HIGHER EDUCATION INSTITUTION - Jooste, K (South African Journal of Higher Education, 2016)
Employing self-directed learning (SDL) methodologies could be advantageous to learner nurses, that are associated with improvement in the affective and psychomotor domains. Despite the efforts to expose students to SDL in a school of nursing in the Western Cape, the challenge remains the lack of students’ self-motivation to SDL during clinical activities in the simulated skills laboratory. This paper focuses on the perceptions of first year learner nurses on learning motivation (as part of a larger study) in self-directed learning activities in a skills laboratory. An exploratory descriptive quantitative design was used. A sample of 168 respondents was selected through simple random sampling. A self-administered 5-point Likert scale questionnaire was developed. Data was gathered an then analysed by using the Statistical Package for the Social Sciences (SPSS) Version 21 software. Descriptive statistics were used to present the findings. It was found that learners were self-motivated to learn with some challenges during the implementation of self-directed learning.